Avaliação da colaboração em empresas participantes de arranjos produtivos locais - Faustino, Cinthia de Azevêdo (2017)
The formation of business arrangements became a strategy adopted by companies to acquire combined benefits that could not be generated individually. Thus, collaboration emerges as a fundamental characteristic in setting and maintaining interorganizational relationships. Local productive arrangements (APLs), known in the international literature as clusters or industrial districts, are widely discussed in several aspects, for instance, their taxonomy. However, there are research gaps that demand new investigations, such as the collaboration between firms in this type of arrangement. There are papers that discuss the benefits that companies can achieve from collaborative interorganizational relationships, but, in addition, it is necessary to create mechanisms to assess the collaboration level in order to assist managers in decision-making. Therefore, this work aims to develop a model to assess the collaboration in companies participating in APLs, testing it through case studies in five companies of a furniture APL in the state of Paraíba. The proposed model used a support tool named Graph Theoretic Approach (GTA), which was combined with the Delphi technique applied to experts in order to define the interrelationships between attributes. The attributes from literature were classified as assessment factors and sub-factors, by the following hierarchical relationships: governance factor (constituted by sub-factors public policies, institutions support and risks and rewards sharing); geographical proximity factor (constituted by sub-factors tangible resources sharing, information sharing and knowledge sharing); and trust factor (constituted by sub-factors informal links, long-term relationship and reputation). Through qualitative-quantitative analysis, it was identified that, in general, the evaluated companies are in the average level of collaboration, according to the classification scale that was developed. The application of the model contributes to encouraging companies to develop collaborative practices for factors with lower levels. As a result, the proposed model can be considered appropriate for its purposes, allowing a general evaluation of the collaboration in companies that work in APLs.